Reinterpreting Iddah Through Family Resilience Theory: Socioeconomic Experiences of Widows in Rural Indonesia - Chelsa Lathifa Annada; Layyin Mahfiana; Riffat Shahzady (Al-Syakhsiyyah: Journal of Law and Family Studies, 2026)
This study investigates the challenges widows face during the iddah period following their husbands' deaths in Ngawen Village, Klaten Regency, Indonesia, with particular attention to differences in occupational background and educational level. Employing a qualitative case study design, the research collected primary data through semi-structured, in-depth interviews with purposively selected participants, including homemakers, small traders, and informal workers. These data were complemented by documentary analysis and village demographic records. The findings were analyzed using content analysis grounded in Froma Walsh’s family resilience theory. The study reveals that widows experience distinct forms of vulnerability and adaptation depending on their socioeconomic background. Homemakers tend to rely heavily on extended family support, traders demonstrate flexible economic coping strategies, while informal workers undergo significant personal transformation to sustain family survival. Adaptation mechanisms also include participation in socio-religious activities and the application of the principle of al-dlarurat tubih al-mahzhurat to negotiate between religious norms and practical necessities. This study contributes empirically to the limited scholarship on iddah in rural Muslim communities. Theoretically, it supports a contextual reinterpretation of the Islamic Law Compilation (KHI) that remains aligned with the substantive objectives of sharia while strengthening widow resilience and community-based support systems.